1994
DOI: 10.1109/18.340469
|View full text |Cite
|
Sign up to set email alerts
|

On information rates for mismatched decoders

Abstract: Reliable transmission over a discrete-time memory-less channel with a decoding metric that is not necessarily matched to the channel (mismatched decoding) is considered. It is assumed that the encoder knows both the true channel and the decoding metric. The lower bound on the highest achievable rate found by Csiszar and Komer and by Hui for DMC's, hereafter denoted C,,, is shown to bear some interesting information -theoretic meanings. The bound C,<, turns out to be the highest achievable rate in the random co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(67 citation statements)
references
References 23 publications
1
66
0
Order By: Relevance
“…An information-theoretic analysis of the NLS channel is cumbersome because of a complicated signal-noise interaction caused by the interplay between the nonlinearity and the dispersion [2]. In general, capacity analyses of optical fibers are performed either by considering simplified channels, or by evaluating mismatched decoding lower bounds [3] via simulations (see [4] and ( [5], Sec. I) for excellent literature reviews).…”
Section: Introductionmentioning
confidence: 99%
“…An information-theoretic analysis of the NLS channel is cumbersome because of a complicated signal-noise interaction caused by the interplay between the nonlinearity and the dispersion [2]. In general, capacity analyses of optical fibers are performed either by considering simplified channels, or by evaluating mismatched decoding lower bounds [3] via simulations (see [4] and ( [5], Sec. I) for excellent literature reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Lapidoth [59] showed that -capacity can equal the channel capacity even if the above lower bound is strictly smaller. Other recent works addressing the problem of -capacity or its special case of zero undetected error capacity include Merhav, Kaplan, Lapidoth, and Shamai [67], Ahlswede, Cai, and Zhang [9], as well as Telatar and Gallager [77].…”
Section: Related Further Resultsmentioning
confidence: 99%
“…(2.5) For equally likely codewords, this decoder finds the most likely codeword as long as the metric q(x, y) is a bijective (thus strictly increasing) function of the transition probability P Y |X (y|x) of the memoryless channel. Instead, if the decoding metric q(x, y) is not a bijective function of the channel transition probability, we have a mismatched decoder [41,59,84].…”
Section: Channel Model: Encoding and Decodingmentioning
confidence: 99%
“…As suggested in the previous chapter, BICM can be viewed as a coded modulation scheme with a mismatched decoding metric. We study the achievable information rates of coded modulation systems with a generic decoding metric [41,59,84] and determine the so-called generalized mutual information. We also provide a general coding theorem based on Gallager's analysis of the error probability by means of the random coding error exponent [39], thus giving an achievable rate and a lower bound to the random coding error exponent.…”
Section: Information-theoretic Foundationsmentioning
confidence: 99%
See 1 more Smart Citation